2021
DOI: 10.3389/fnins.2021.760567
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Finger Proteins in Neuro-Related Diseases Progression

Abstract: Zinc finger proteins (ZNF) are among the most abundant proteins in eukaryotic genomes. It contains several zinc finger domains that can selectively bind to certain DNA or RNA and associate with proteins, therefore, ZNF can regulate gene expression at the transcriptional and translational levels. In terms of neurological diseases, numerous studies have shown that many ZNF are associated with neurological diseases. The purpose of this review is to summarize the types and roles of ZNF in neuropsychiatric disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 148 publications
2
48
0
Order By: Relevance
“…The main function of ZFs in the brain is to promote the development of different parts of the brain and the differentiation of neural stem cells. Many studies have shown that ZFPs are closely related to the pathogenesis of nervous system diseases [ 170 ]. Researchers found that many ZFP DNA-binding domains downregulated the transcriptional activity of nr2f through missense mutations, to regulate cognitive impairment and optic nerve atrophy [ 171 ].…”
Section: Zfp and The Cellular Pathwaysmentioning
confidence: 99%
“…The main function of ZFs in the brain is to promote the development of different parts of the brain and the differentiation of neural stem cells. Many studies have shown that ZFPs are closely related to the pathogenesis of nervous system diseases [ 170 ]. Researchers found that many ZFP DNA-binding domains downregulated the transcriptional activity of nr2f through missense mutations, to regulate cognitive impairment and optic nerve atrophy [ 171 ].…”
Section: Zfp and The Cellular Pathwaysmentioning
confidence: 99%
“…On the other hand, TTP has an increased expression in TC samples compared to healthy controls. So far, studies on other types of zinc-finger family proteins (C2H2 type, MYM type, ZC3H14 type, and Matrin type) have been performed in AD (reviewed in Bu et al, 2021 ). Meanwhile, MSUT2 (ZC3H14), belonging to the CCCH family, ultimately affects the accumulation of tau proteins to affect NFTs ( Baker et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The zinc-finger units regulate gene expression at the transcriptional and translational levels and are highly expressed in the brain (48). It has already been demonstrated that zinc-finger genes are associated with pathological changes in AD and regulate the expression of AD-related genes that are upstream in the production of hyperphosphorylated tau (49). This could explain the positive association when integrating [ 18 F]FDG-PET and zinc-finger-related regulatory units enriched with DEGs.…”
Section: Discussionmentioning
confidence: 99%